COMPOSITION OF THE CATCHING OF RINGS TRAINS (PURSE SEINE) AT THE FISHING PORT OF KUTARAJA OCEAN ACEH PROVINCE - Yomi Tri Satria; Bustari Bustari; Nofrizal Nofrizal (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Purse Seine is one of the dominant fishing gear used by fishermen at the Kuta Raja Aceh Ocean Fishery Port. However, it is not yet known how the composition andamount of the main and by-catch using ring trawl fishing gears in the waters of theLampulo Ocean Fishing Port is unknown. This study aims to identify the composition ofPurse seine catches based on Main catch and By-catch. This research was conducted inJuly - August 2020 at the Kuta Raja Ocean Fishing Port, Aceh Province.The method usedin this study is a direct survey method which includes primary data and secondary data.The results showed that the fish catches at the Kuta Raja Lampulo Ocean Fishing Port in2015-2019, the peak of the annual catch occurred in 2019 with a total of 1,646,832 kg.Furthermore, the lowest catch at the Kuta Raja Lampulo Ocean Fishing Port occurred in2015 with a total of 956,350 kg. Composition The main catch of the entire Purse seineconsisted of skipjack (Katsuwonus pelamis) as much as 2,761,857 kg, yellowfin tuna(Thunnus albacares) as much as 1,116,715 kg, tuna krei fish (Auxis thazard) as much as250,571 kg. Furthermore, by-catch fish are goat-goat fish (Albalistes stellaris) as much as97,375 kg, scad fish (Decapterus macrosoma) as much as 1,768,209 kg, lisong fish (Auxisrochei) as much as 441,436 kg, selar fish (Selaroides leptolepis) as much as 41,361,siro/lemuri fish (Saridinella lemuru) as much as 40,892 kg, sunglir fish (Elagatisbipinulatus) as much as 51,283 kg and komo tuna (Euthynnus affinis) as much as 35,310.